バイリンガルの内的表象に関するカテゴリー群化を用いた構造化の検証 - 箱田, 裕司; 榊, 祐子 (心理学研究, 2013)
This study provides evidence for the organization of bilingual conceptual representations in terms of second-language proficiency and the similarity between the two languages. Two bilingual groups (Japanese-English and Japanese-Korean) of participants were assigned a free recall task with a category list. The list consisted of 36 items from different levels of typicality, which were presented in the first or second language. The occurrence of category clustering varied according to typicality for the two groups. Among Japanese-English participants, Japanese representations were better organized than English items for participants with less-proficient levels of English, but this changed to a semantic network between the two languages with increasing second-language proficiency. Conversely, Japanese-Korean bilinguals established a semantic network with the two languages even at the beginner level with the second language. These findings indicate that both similarity between languages and second-language proficiency exert a strong effect in constructing a network in conceptual systems.